Design of dexterous hands based on parallel finger structures. (October 2020) - Jin, Xiaodong; Fang, Yuefa; Zhang, Dan; Gong, Junshan
Highlights: Two types of parallel fingers are designed by structural evolution associated with Lie group deduction. Two novel 3-finger dexterous hands with parallel finger structures are proposed. The dexterous hands have much higher carrying capacity due to their parallel finger structures. The dexterous hands have high task adaptability and large finger workspace. The dexterous hands are able to manipulate the object in planar 3-DOF and spatial 6-DOF, respectively. Abstract: The dexterous hands with high dexterity, high carrying capability, high precision and high task adaptability (multipurpose) are demanded in industry. This paper focuses on designing dexterous hands based on the parallel finger structures to improve above performances. Based on the motion property of human finger, the required motion types of the dexterous hands are proposed. The finger structures of RR-RPR and 2-UU-UPU are presented by structural evolution from the well-known PMs of parallelogram and 3-UU by means of group deduction, respectively. Two three-finger dexterous hands are designed by assembling the obtained parallel fingers on the palm in the same direction. The in-hand configurations are actually hybrid mechanisms, whose motion properties are analyzed by equivalent to the parallel mechanisms (PMs). The hands have high task adaptability that can perform the pinching operations both from the outside and inside the cavity of the objects. The kinematics of the fingers are presented to investigate the workspace performance, and the statics are analyzed to prove that the proposed parallel dexterous hands can provide desirable pinching force.